SOSIALISASI PERATURAN DAERAH NO. 8 TAHUN 2013 TENTANG PENGELOLAAN SAMPAH KABUPATEN SIJUNJUNG KECAMATAN SIJUNJUNG - Yanesa, Anggella; Sahuri, Chalid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Given the tremendous amount of waste generated per day would need to be an attempt to address the problem, the Government Sijunjung District of Sijunjung make a socialization to overcome the problem, namely the Regional Regulation No. 08 of 2013 on the management of waste that aims to improve public health and environmental quality and to utilize waste as a resource. Trash that are produced by the District Sijunjung community is for household waste or household with a percentage of 77.89% of organic waste is carried out 2-4 times a day to transport it to the landfill.The purpose of this study were (a) to identify and analyze the socialization of implementation of Regional Regulation No. 08 of 2013 concerning waste management in Sijunjung, (b) to determine and describe the factors that become an obstacle to the socialization of the implementation of the Regional Regulation No. 08 of 2013 on waste management in Sijunjung. This research was conducted at the Environment Agency Sijunjung who socialize regulation No. 08 of 2013 on waste management, accordance with the object mentioned above, the necessary data technique election informants in this research is purposive sampling, while the informants in this study is as follows: Head of the Environment Agency, Section of Environment, Head of Environmental Degradation Control, Sub Division of Administration, the District Public Sijunjung Sources of data in this study are primary data and secondary data. For the technique of data collection was done by interview, observation and literature study. Methods of data analysis used in this study is a qualitative descriptive analysis.From the results of research on the area of socialization Regulations No. 8 of 2013 on Waste Management, especially in Sub Sijunjung seen from the aspect of communication, resources, attitude or disposition as well, bureaucratic structure. The obstacles encountered in the implementation of the socialization of Bylaw No. 8 of 2013 on Waste Management in Sub Sijunjung among others: (a) lack of ability and profesonalisme human resources to carry out the implementation of waste management, (b) the lack of facilities and infrastructure that support the implementation of waste management, (c ) lack of employee attitudes for interaction, communication and coordination between authorities in conducting waste management, (d) lack of coordination, performed the Environment Agency with other relevant agenciesKeywords: Socialization, Bylaw No. 8 of 2013 On Waste Management